2016
DOI: 10.2147/clep.s99504
|View full text |Cite
|
Sign up to set email alerts
|

The Danish Heart Failure Registry

Abstract: Aim of databaseThe aim of the Danish Heart Failure Registry (DHFR) is to monitor and improve the care of patients with incident heart failure (HF) in Denmark.Study populationThe DHFR includes inpatients and outpatients (≥18 years) with incident HF. Reporting to the DHFR is mandatory for the Danish hospital departments treating patients with incident HF. Final decision to register a patient in the DHFR is made by a cardiologist to ensure the validity of the diagnosis. Approximately 42,400 patients with incident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(48 citation statements)
references
References 10 publications
0
48
0
Order By: Relevance
“…In the Danish cohort, hospital departments adhered well to the required annual standard benchmark set by the Danish Heart Failure Database (DHFD) audit commission to maintain one-year mortality at or less than 20% [ 23 ]. We found that the rate of one-year mortality in incident HF patients became even smaller during the three audit years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the Danish cohort, hospital departments adhered well to the required annual standard benchmark set by the Danish Heart Failure Database (DHFD) audit commission to maintain one-year mortality at or less than 20% [ 23 ]. We found that the rate of one-year mortality in incident HF patients became even smaller during the three audit years.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained data from the DHFD on 12,001 patients with incident heart failure defined by the following (International Classification of Diseases ICD-10) codes: I 11.0, I 13.0, I 13.2, I 42.0, I 42.6, I 42.7, I 42.9, I 50.0, I 50.1, and I 50.9 [ 1 , 23 ]. The patients were 18 years or older and were newly diagnosed with HF upon hospitalization for the first time (at either an out- or inpatient department) between 21 June 2010 and 30 June 2013 (this period covers three audit years).…”
Section: Population and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…New registries and data analysis processes have been developed in diverse fields, in response to PQRS [27‐29]. Quality‐of‐care registries also are taking shape internationally; examples include the National Clinical Audit and Patient Outcomes Programme in the United Kingdom [30], the Burns database in New Zealand [31], and the Danish Heart Failure Registry [32]. New frameworks are being developed for EHR‐based measurement of quality of care; these efforts have to work through unrealistic expectations among stakeholders that quality‐of‐care measurement is easy in EHRs, challenges of the types outlined previously, and new difficulties that arise from the electronic quality‐of‐care data collection and measurement processes themselves [33].…”
Section: Introductionmentioning
confidence: 99%